Predicting earnings and cash flows: The information content of losses and tax loss carryforwards - Sandra Dreher; Sebastian Eichfelder; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
We analyse the relevance of losses, accounting information on tax loss carryforwards, and deferred taxes for the prediction of earnings and cash flows up to four years ahead. We use a unique hand-collected panel of German listed firms encompassing detailed information on tax loss carryforwards and deferred taxes from the tax footnote. Our out-of-sample predictions show that considering accounting information on tax loss carryforwards and deferred taxes does not enhance the accuracy of performance forecasts and can even worsen performance predictions. We find that common forecasting approaches that treat positive and negative performances equally or that use a dummy variable for negative performance can lead to biased performance forecasts, and we provide a simple empirical specification to account for that issue.
urn:nbn:de:gbv:3:2-83624
Keywords: C53; M40; M41; 330; performance forecast; in-sample prediction; out-of-sample prediction; loss persistence; deferred taxes; tax loss carryforwards